UPAYA PENINGKATAN LITERASI BACA DAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL CIRC SISWA SEKOLAH DASAR - Andrimeta Pramudewayanti; Endang Indarini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze efforts to improve reading literacy and learning outcomes in Pancasila Education through the implementation of the Cooperative Integrated Reading and Composition (CIRC) model among fifth-grade students at SD Negeri Bergaskidul 04. The background of this research is the low level of reading literacy and student achievement, particularly in Pancasila Education, as reflected in national assessment data and the 2025 education report. The study employs Classroom Action Research (CAR) using the Stringer model, which consists of three stages: look, think, and act, and is carried out in two cycles, each consisting of two meetings. Data were collected through observation of teacher and student activities, reading literacy tests, and learning outcome evaluations.The results showed a significant improvement in students’ reading literacy and learning outcomes after the implementation of the CIRC model. The average teacher activity score increased from 86 in the first cycle to 90% in the second cycle, while the average student score rose from 75.5 to 84. The percentage of students meeting the learning objectives criteria also increased sharply, from 17% in the first cycle to 91% in the second cycle. The improvement in students’ reading literacy was evident in all aspects, such as the ability to find content, obtain information, interpret, classify, and conclude. The CIRC model proved effective in encouraging collaboration, increasing motivation, and strengthening students’ understanding of Pancasila Education material.This research provides a theoretical contribution to the development of cooperative learning models, as well as practical benefits for teachers, students, principals, and future researchers. It is recommended that the CIRC model be implemented sustainably to improve the quality of learning and reading literacy in elementary schools.